2022
DOI: 10.1262/jrd.2021-084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the preservation medium and storage duration of domestic cat ovaries on the maturational and developmental competence of oocytes <i>in vitro</i>

Abstract: We examined the effectiveness of saline, Euro-Collins solution (EC), and ET-Kyoto solution (ET-K) as preservation media for the cold storage of feline ovaries. Ovaries were maintained in these media at 4 °C for 24, 48, or 72 h until oocyte retrieval. The ET-K group exhibited a higher oocyte maturation rate than the saline group after 72 h of storage. Moreover, ET-K could sustain the competence of the feline oocytes to cleave after 48 h, and the morula formation rate of the ET-K group was higher than that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous studies have revealed that adding sugar to an extender positively impacts the motility, vitality, and plasma membrane integrity (PMI) of mammalian semen after cryopreservation [ 6 – 9 ]. Various studies used fructose or glucose in a tris-citric acid diluent to freeze mammalian sperm [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that adding sugar to an extender positively impacts the motility, vitality, and plasma membrane integrity (PMI) of mammalian semen after cryopreservation [ 6 – 9 ]. Various studies used fructose or glucose in a tris-citric acid diluent to freeze mammalian sperm [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…During freezing, the sperm are exposed to a wide range of temperatures, which causes structural and functional changes. So, for long-term sperm preservation until artificial insemination, the spermatozoa need an extender containing appropriate cryoprotectants, a sufficient quantity of nutrients, a well-buffered agent like tris, and a cold shock protector like egg yolk during the storage in liquid nitrogen [ 9 , 25 – 31 ]. Moreover, cryopreservation still causes semen damage in various animals [ 32 , 33 ], and researchers are still determining the optimum ingredient levels of the semen extender for freezing buck semen.…”
Section: Discussionmentioning
confidence: 99%
“…During semen cryopreservation, any changes in pH could affect the metabolism rates, motility, viability, and plasma membrane integrity [ 34 , 35 ]. Sodium citrate, HEPES, bicarbonate, and tris have been used as pH controllers to maintain the pH in the extender [ 9 , 19 , 25 ]. The pH of tris is representative of most living cells.…”
Section: Discussionmentioning
confidence: 99%
“…O uso dos oócitos de espécies domésticas para o entendimento da maturação in vitro de gametas contribui para o conhecimento e melhoria das técnicas de reprodução assistida em fêmeas ruminantes (EL-SOKARY et al, 2022;MASTROROCCO et al, 2021), conservação de animais em extinção como as espécies carnívoras, as quais utilizam ovários de fêmeas caninas e felinas domésticas como modelo (YOSHIDA et al, 2022;VIARIS DE LESEGNO, et al, 2008).…”
Section: Introductionunclassified